(untitled) (International journal of medical sciences, 2026)
This article discusses the working principle of lasers and their underlying physical foundations. The formation of laser radiation is explained based on the concepts of stimulated emission, population inversion, and the optical resonator. The main components of a laser system, including the active medium, energy source, and resonator, are also examined. In addition, the article provides a brief overview of different types of lasers and their practical applications.